2012
DOI: 10.1590/s1982-56762012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Diaporthe phaseolorum var. caulivora (causal agent of soybean stem canker) artificially inoculated in different crop residues

Abstract: Stem canker caused by Diaporthe phaseolorum var. caulivora is an important disease of soybean in Argentina. The objective of this study was to determine its survival ability in artificially infested straw under laboratory and field conditions. In laboratory, stem pieces of soybean, maize, sorghum, sunflower, potato and wheat were autoclaved, placed in petri dishes on Potato Dextrose Agar and Water Agar, and inoculated with a 7-day-old pathogen culture. All crop residues were colonized and produced perithecia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…caulivora did not reproduce asexually in this study. However, the same finding had been already reported in Argentina (Grijalba and Ridao 2012). Albeit it is also observed that D. caulivora can seldom produce pycnidia (Santos et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…caulivora did not reproduce asexually in this study. However, the same finding had been already reported in Argentina (Grijalba and Ridao 2012). Albeit it is also observed that D. caulivora can seldom produce pycnidia (Santos et al 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Consistently, trichomes are preferred penetration sites for several fungi, facilitating adhesion of fungal spores and hyphae, and allowing fungal colonization progress on the tissue surface (Lazniewska et al, 2012). Ascospores on infected soybean and crop residue are the main source of inoculum (Grijalba and Ridao, 2012), and our results suggest that hyphae from germinated ascospores could be associated with trichomes. After inoculation, D. caulivora started to colonize the cortex at 24 hpi, progressed, and reached the phloem at 48 hpi and the xylem at 72 hpi.…”
Section: Discussionsupporting
confidence: 75%
“…In 2002, D. caulivora was widely disseminated in the main soybeanproducing region of Argentina, where it coexists with D. aspalathi (Pioli et al, 2002). At present, D. caulivora is considered the predominant pathogen causing SSC in Argentina (Grijalba and Guillin, 2007;Grijalba and Ridao, 2012). The high number of D. caulivora isolates in soybean stems with canker lesions also suggests the dissemination of this pathogen in Uruguay.…”
Section: Discussionmentioning
confidence: 99%
“…The ascospores cause the first infections of young stems in spring and all subsequent infections. The fungus could maintain alive in hosts for at least 6-7 months [12]. On susceptible varieties, it can cause losses of up to 50% of the hosts.…”
Section: Resultsmentioning
confidence: 99%